Análise da institucionalização do Programa de Aquisição de Alimentos (PAA) na CEAGESP: o caso do CEASA de Araraquara (SP) - Realino, Marco Aurélio Assunção (Universidade Federal de São Carlos, 2016)
The food security issue has entered the public agenda after the World War II, when some countries started acting to eradicate poverty and hunger (SIMON, 2012). In Brazil, the issue became relevant after 2003, when the government made some policies to end the hunger as well as poverty, like the Programa de Aquisição de Alimentos (PAA). Thus, this research aims to analyze the possibility of the implementation of PAA in Companhia de Entrepostos e Armazéns Gerais de São Paulo (CEAGESP), which is a public company responsible for storage services and wholesale food market in São Paulo state. The analysis was first focused on the Ceasa Araraquara unity, as a diagnosis which can be applied on the other unities later. Therefore, some interviews were conducted with the managers of some CEAGESP's unities along with secondary data. The theorical referential was based on the Strategic Action Fields, to understand the power relations inside the fields of food secure. To lead a better understanding of the food secure policies it was made an historical analysis of the issue, first in a worldwide context and later in a national level. Finally, the results show primarily that the operation of the PAA by CEAGESP finds some barriers within political issues. Once those questions are overcome, it will become possible for the public company to execute the policy.
Keywords: Segurança alimentar e nutricional; CEASA de araraquara; Mercado institucional; Food Security Policy; Institutional Market; CIENCIAS SOCIAIS APLICADAS::ADMINISTRACAO::ADMINISTRACAO PUBLICA::ORGANIZACOES PUBLICAS